Mobile Technology and University Climate: Impact on Academic Well-Being - Ibrahim, Asem M.; Al Daabseh, Tariq K. I.; Teleb, Ahmed A.; Abdelmagid, Ahmed S.; Soliman, Amro M. (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study explores the complex relationship between mobile technology, perceived university climate quality (PUCQ), and their combined impact on predicting students’ academic subjective well-being (ASW) at King Khalid University (KKU). The research aimed to identify the nature of the correlation between the PUCQ and ASW and to verify the degree of the relative contribution of the PUCQ in predicting ASW among KKU students. To achieve the objectives of the study, a descriptive approach was employed, incorporating both correlational and comparative methods. The researchers prepared a measure of PUCQ and a measure of ASW for university students. The research sample consisted of 134 students, with an equal split of 67 males and 67 females, whose ages ranged from 18 to 45 years. They belonged to various programs at KKU. Pearson’s correlation coefficient, simple regression analysis using the Enter method, and multiple regression analysis using the stepwise method were employed for data processing. The results of the study revealed a statistically significant positive correlation between the PUCQ and the values of citizenship. In addition, the PUCQ in its three dimensions contributes to predicting ASW among the research sample. In an era dominated by mobile technology, understanding its role is pivotal for creating a positive and supportive academic environment at King Khalid University.